The toxicity of cooking oil fumes on human bronchial epithelial cells through ROS‐mediated MAPK, NF‐κB signaling pathways and NLRP3 inflammasome. Issue 5 (21st January 2022) - Liu, Jianli; Fu, Mingyang; Miao, Jingyi; Sun, Yueling; Zhu, Rugang; Liu, Chengying; Bi, Ruochen; Wang, Shuai; Cao, Xiangyu
Abstract: Cooking oil fumes (COFs) are the main pollutants in kitchen and indoor air, which threaten human health. Exposure to COFs may lead to respiratory diseases and impair pulmonary function. To investigate the toxicity of COFs on human bronchial epithelial cells (Beas‐2B) and explore the underlying mechanisms, MTT assay was conducted to detect the viability of Beas‐2B. Intracellular reactive oxygen species (ROS) levels and nitric oxide (NO) levels were determined with DCFH‐DA assay and DAF‐FM assay. The expression of genes involved in inflammation were measured with quantitative real‐time PCR (qRT‐PCR). The phosphorylation and the expression of proteins related to Mitogen‐activated protein kinase (MAPK), NF‐κB signaling pathways were measured with western blot. Our results revealed that COFs decreased cell viability, increased the ROS levels and NO levels and induced apoptosis in Beas‐2B cells. The results of qRT‐PCR and western blot showed that the expression of NLRP3, p65, iNOS, IL‐1β, and the factors related to oxidative stress and inflammation increased, NF‐κB signaling pathway and MAPK signaling pathway were activated. This study provided some useful information to evaluate the toxicity of COFs and revealed the possible mechanism for the damage on respiratory system induced by COFs.